Sinergitas Stakeholders dalam Perspektif Good Governance (Studi Pada Program Malang Green, Clean, and Save di Kota Malang) - Mohammad Jamhar Hamsa Asyhari (Jurnal Administrasi Publik, 2016)
Abstract: Stakeholders synergy in the Perspective of Good Governance (Study in the Malang Green, Clean, and Save Program in Malang City). Malang Green, Clean, and Save program born with the hope to be a solution in addressing environmental issues in Malang. Stakeholders synergize in Malang Green, Clean, and Save program are Radar Malang as the leader and originator of the program, and Sanitation Department (DKP) Malang, PT. Indana Paint and Malang society at large. Stakeholders synergize combine a wide range of interests of each stakeholder showed in six events on the agenda of the Malang Green, Clean and Save program such as, green village competition, green school competition, miss environmental competition, Malang clean movement, housewifes gobak sodor competition, pos kamling competition. Synergy of stakeholders in the Malang Green, Clean, and Safe program at once show the Malang city government's efforts to achieve good governance that not only the government as a single actor in governance, but rather involve various parties concerned, both private and public. Keywords :Sinergy, Stakeholders, Malang Green Clean  and Save program, Good Governance, Malang City     Abstrak:Sinergitas Stakeholders dalam Perspektif Good Governance (Studi Pada Program Malang Green, Clean, and Save di Kota Malang). Program  Malang Green, Clean, and Save lahir dengan harapan dapat menjadi sebuah solusi dalam mengatasi permasalahan lingkungan di Kota Malang. Stakeholders yang bersinergi dalam Program Malang Green, Clean, and Save adalah Radar Malang sebagai pimpinan dan pencetus program, Dinas Kebersihan dan Pertamanan (DKP) Kota Malang, PT. Indana Paint, dan masyarakat Kota Malang secara luas. Sinergitas stakeholders menyatukan berbagai kepentingan dan melahirkan enam kegiatan sebagai agenda dari Program Malang Green, Clean and Save meliputi lomba kampung hijau, lomba sekolah hijau, lomba putri lingkungan, gerakan bersih Kota Malang, lomba gobak sodor ibu-ibu, dan lomba pos kampling. Sinergitas stakeholders dalam Program Malang Green, Clean, and Save juga sekaligus menunjukkan upaya pemerintah Kota Malang untuk mencapai Good Governance yang tidak hanya pemerintah sebagai aktor tunggal dalam penyelenggaraan pemerintahan, melainkan melibatkan berbagai kalangan yang berkepentingan baik swasta maupun masyarakat.   Kata kunci: Sinergi, Stakeholders, Program Malang Green, Clean, and Save, Good Governance, Kota Malang